Analysis of the results of acoustic emission diagnostics of a structure during helicopter fatigue tests. Issue 2 (3rd April 2017) - Urbahs, Aleksandrs; Carjova, Kristine; Fescuks, Jurijs
Abstract: The study is devoted to a perspective diagnostic method, which makes it possible to deal with diagnostic tasks – the acoustic non-destructive inspection method based on acoustic emission (AE) signal parameter analysis. The practical use of this method is related to the interpretation of diagnostic measurement data. The parameters of acoustic emission (AE) signals were measured during bench tests of the tail boom structure and fin, as well as the joint areas of the fin, tail boom, and fuselage of the helicopter (joint area No.1 and No.19, frames of the tail boom and fuselage respectively).The analysis of fatigue damage kinetics was carried out in several stages for groups of bolts and for characteristic structure loading intervals. Bolt fracture was predicted at least 26 to 44 flight hours before the actual collapse. Using the AE parameters, the micro crack origin intervals identified when the bolt bearing capacity after the occurrence of the damage reached 96%.